Muscle atrophy in lung cancer cachexia: towards a living single muscle fiber approach (2025)
Introduction: Cancer is a major public health challenge because of its high prevalence, morbidity, mortality, and healthcare costs. Among its systemic complications, cancer-induced cachexia (CC) is particularly debilitating, further hindering cancer treatments and predicting poor prognosis (WHO, 2019; Fearon et al. 2011; Lim et al. 2020). Despite this, the CC pathophysiology remains poorly understood at the muscle cellular level. Here, we develop a single-muscle fiber murine model with potential to address CC cellular mechanisms. Materials & Methods: One million Lewis Lung Carcinoma (LLC1, ATCC-CRL: 1642) cells (passage 4) were injected into Tumor-Bearing (TB) C57BL/6 adult mice (3 males, 3 females). Controls (2 males, 2 females) received phosphate buffered saline. Body weight, temperature, thigh and calf circumferences, and tumor diameter were repeatedly measured. After 241.8 days, mice (10.350.25 weeks old) were sacrificed. Tumors, liver, heart, spleen, fat depots (retroperitoneal, visceral, epididymal), and muscles (Flexor Digitorum Brevis (FDB), Peroneus Longus (PL), Extensor Digitorum Longus (EDL), Plantaris, Soleus) were dissected and weighed. Muscles were dissociated in collagenase type II; only isolated, well-contracting fibers were imaged and morphometric analyses were performed using ImageJ. Results: Control animals gained 2.390.54 g but TB mice lost 1.151.6 g (p=0.006). Thigh and calf circumferences tended to decrease, but spleens were significantly heavier in TB mice (162.677.16 mg) compared to controls (57.3510.01 mg; p=0.037). The greatest difference in fat tissue was observed in the visceral depot (mg): control 329.85117.19, TB 233.62105.70, though not significant (p=0.318). Regarding muscle tissue weight, the greatest change was observed in the EDL (mg): control 9.531.45, TB 8.071.24 (p=0.190). The FDB, EDL and PL fibers of TB mice showed a 20.810.5% (p=0.01) lower diameter (n=199) than the control ones (n=111). The Soleus fibers remained unaffected (p=0.521) Conclusion: The decreases in weights and circumferences, as well as the splenomegaly, confirm the development of inflammation and CC in the TB mice. This study offers the first evidence of muscle atrophy at the single-fiber level in a CC murine model, paving the way for future detailed physiological, biophysical, molecular and mathematical studies of living single skeletal muscle fibers in the context of CC (CODI 2021-40170; FUA-001-2024/2025-0072).